Coupling phosphate-solubilizing bacteria (PSB) with inorganic phosphorus fertilizer improves mungbean (Vigna radiata) phosphorus acquisition, nitrogen fixation, and yield in alkaline-calcareous soil. Issue 3 (March 2022) - Khan, Hamid; Akbar, Waqas Ali; Shah, Zahir; Rahim, Hafeez Ur; Taj, Ali; Alatalo, Juha.M.
Abstract: To overcome the problems associated with soil phosphorus (P) insolubility, soil inoculation with phosphate-solubilizing bacteria (PSB) can be used. In a field experiment, we evaluated the efficacy of PSB in enhancing mungbean P acquisition, nitrogen (N) fixation, and morphological and yield traits in alkaline-calcareous soil when added together with P as single superphosphate (SSP) or rock phosphate (RP) at 45 or 90 kg P2 O5 ha −1 . Coupling PSB with mineral P fertilizers (SSP & RP) improved P use efficiency, mungbean P acquisition, N2 fixation, nodulation, NP uptake, and the morphological and yield-related traits of mungbeans compared with non-fertilized controls and plots received P from mineral sources alone. Soil PSB inoculation with mineral P also improved post-harvest soil fertility relative to pre-harvest by improving soil organic matter from 0.61% to 0.70%, lowering pH from 7.74 to 7.68, and improving soil total N from 0.04 to 0.09%, ABDTPA-extractable P from 2.07 to 3.44 mg kg −1, and potassium (K) concentrations from 100.27 to 129.45 mg kg −1 . When combined with PSB, RP generally performed better than SSP. Moreover, there was a significant correlation between soil N and plant N, while the correlation between soil P and plant P was non-significant. The correlation between soil organic matter content and NP uptake by mungbeans was also non-significant. Therefore, adding P as RP at 45–90 kg ha −1, together with PSB inoculation, can be recommended for improving mungbean P acquisition, use efficiency, optimum N2 fixation, and yield in alkaline-calcareous soils. Abstract : Phosphate-solubilizing bacteria (PSB); Mineral phosphorus; Mungbean phosphorus acquisition; Nitrogen fixation; Yield, Alkaline-calcareous soils.